2005
DOI: 10.1603/0022-2585(2005)042[1020:rpbeaa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Roles Played by Esterase Activity and by a Sodium Channel Mutation Involved in Pyrethroid Resistance in Populations of <I>Boophilus microplus</I> (Acari: Ixodidae) Collected from Yucatan, Mexico

Abstract: Pyrethroid resistance in Boophilus microplus (Canestrini) (Acari: Ixodidae) was studied by correlating discriminating-dose (DD) bioassay results and esterase activity or the frequency of a sodium channel mutation known to be involved in pyrethroid resistance in nine field strains of B. microplus from Yucatan, Mexico. Two tick strains (P67 and B74) were identified as susceptible to cypermethrin, deltamethrin, and flumethrin by DD, one strain (P65) was susceptible to cypermethrin and resistant to deltamethrin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 17 publications
4
22
0
4
Order By: Relevance
“…A PCR diagnostic assay (GUERRERO et al, 2001) was developed that allowed the rapid detection of this amino acid substitution in individual ticks, larvae or eggs. Large numbers of ticks were assayed by this method and this target site mechanism was found to be widespread throughout Mexico (ROSARIO-CRUZ et al, 2005 and in an outbreak strain in the United States (MILLER et al, 2007). The location of this sodium channel mutation is a bit out of the ordinary, as more arthropod sodium channel pyrethroid resistance-causing mutations are located in Domain II than the other three domains (SODERLUND; KNIPPLE, 2003).…”
Section: Pyrethroid Resistancementioning
confidence: 99%
“…A PCR diagnostic assay (GUERRERO et al, 2001) was developed that allowed the rapid detection of this amino acid substitution in individual ticks, larvae or eggs. Large numbers of ticks were assayed by this method and this target site mechanism was found to be widespread throughout Mexico (ROSARIO-CRUZ et al, 2005 and in an outbreak strain in the United States (MILLER et al, 2007). The location of this sodium channel mutation is a bit out of the ordinary, as more arthropod sodium channel pyrethroid resistance-causing mutations are located in Domain II than the other three domains (SODERLUND; KNIPPLE, 2003).…”
Section: Pyrethroid Resistancementioning
confidence: 99%
“…This is highlighted by an increasing number of infestations in the TEQA and beyond that have been found in recent years to be resistant [19,20]. Nearly all resistant infestations discovered within the U.S. are associated with pyrethroid acaricides, however, resistance to multiple acaricide classes (including coumaphos) has been described in the U.S. [14,19] and Mexico [21,22]. Pyrethroid resistance was first discovered in Mexico in 1994, shortly after the introduction of pyrethroids into the Mexican cattle market in the 1980s [23].…”
Section: Introductionmentioning
confidence: 99%
“…This assay detects a nucleotide difference that causes Phe to Ile amino acid substitution in the S6 transmembrane segment of domain III of the para-like sodium channel, and it clearly distinguishes heterozygotes from homozygotes (GUERRERO et al, 2001). Studies have shown that this mutation correlates with flumethrin, deltamethrin and cypermethrin resistance in Mexican tick populations (JAMROZ et al, 2000;ROSARIO-CRUZ et al, 2005).…”
Section: Introductionmentioning
confidence: 99%